Second-Hand Clothe, a New Threat for Acquiring Parasitic Infection - Arash RAKHSHANPOUR; Abolghasem AGHAHOSSEIN SHIRAZY; Reza SHAFIEI; Mohammad Taghi RAHIMI (Tehran University of Medical Sciences, 2020)
.